Leaflet-Based Learning Media Development in Structural Materials and Function of Class XI Animal Tissues - Eka Widiya Wati; Kaspul Kaspul; Muhammad Arsyad (Master Program of Biology Education, Universitas Lambung Mangkurat, 2020)
The use of instructional media, especially visual media, is very influential in student learning and learning outcomes. The teacher can develop visual learning media so that students can learn well fun and attract learning interest. Experts say that approximately 90% of one's learning outcomes are obtained through vision, 5% from hearing, and 5% from other senses. Development research aims to produce a valid leaflet-based learning media so that it is fit for use by students. This type of research was adapted from Tessmer's design, through the preparation stage (preliminary) and formative evaluation (formative evaluation) with stages only to self-evaluation, and expert testing. The expert opinion includes 3 validators according to expertise. Data was obtained from research instruments in the form of content/material validity evaluation sheets, and construct validity. Data collection techniques using assessment sheets. Analysis of data validity based on the Akbar category (2013). Based on the research results of the first meeting leaflet, the content validity value was 92.05%, and the construct validity was 98.61%. The second meeting leaflet obtained content validity value 92.65%, and construct validity 97.45%. So it was concluded that the learning media of the development leaflet was categorized as very valid.AbstrakPenggunaan media pembelajaran terutama media visual sangat berpengaruh pada pembelajaran dan hasil belajar siswa. Guru dapat mengembangkan media pembelajaran visual agar siswa dapat belajar dengan baik menyenangkan dan menarik minat belajar. Para ahli menyebutkan bahwa kurang lebih 90% hasil belajar seseorang diperoleh melalui penglihatan, 5% dari pendengaran, dan 5% lagi dari indra lainnya. Penelitian pengembangan bertujuan menghasilkan media pembelajaran berbasis leaflet yang valid sehingga layak digunakan oleh peserta didik. Jenis penelitian diadaptasi dari desain Tessmer, melalui tahap persiapan (preliminary) dan evaluasi formatif (formative evaluation) dengan tahapan hanya sampai evaluasi diri, dan uji pakar. Pendapat pakar meliputi 3 validator sesuai keahlian. Data diperoleh dari instrumen penelitian berupa lembar penilaian validitas isi/materi, dan validitas konstruk. Teknik pengumpulan data menggunakan lembar penilaian. Analisis data validitas berdasarkan kategori Akbar (2013). Berdasarkan hasil penelitian leaflet pertemuan pertama memperoleh nilai validitas isi/materi 92,05%, dan validitas konstruk 98,61%. Leaflet pertemuan kedua memperoleh nilai validitas isi/materi 92,65%, dan validitas konstruk 97,45%. Sehingga disimpulkan media pembelajaran leaflet hasil pengembangan masuk kategori sangat valid.